The Legal Status of Children in Unregistered Marriage Divorces:Problems and Challenges - Ramadhani, Indriya; Sulistiyaningsih, Nur; Solikhah (Program Studi Hukum Keluarga Islam Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstrak: Studi ini ditujukan untuk mengkaji status anak dalam perceraian nikah siri sebagaimana Hukum Islam dan Hukum Positif di Indonesia. Dalam perkara ini, suami masih berstatus terikat perkawinan sah bersama wanita lain. Termasuk pada studi hukum normatif dengan pendekatan undang-undang dan kasus, studi ini menerapkan data primer dan sekunder. Melalui teknik studi kepustakaan, data pada studi ini dianalisis dengan metode deduksi silogisme. Temuan studi membuktikan bahwasanya status anak dalam Putusan Nomor 546/Pdt.G/2024/PA.Krw dapat diakui secara hukum sebagai anak kandung Tergugat (Ayah biologis anak/suami siri Penggugat) sesuai dengan alat bukti yang diajukan di pengadilan. Walaupun pada saat menikah, Penggugat (Ibu Anak/istri siri Tergugat) telah hamil dua bulan, anak yang lahir dapat diakui sebagai anak Tergugat (Ayah biologis anak/suami siri Penggugat), sebab syarat bahwa anak dari seorang wanita yang telah hamil pada saat dinikahi sebagaimana Imam Syafi'i dan Imam Malik adalah lahir minimal enam bulan sejak perkawinan dilangsungkan, sedangkan anak dari Penggugat lahir setelah tujuh bulan perkawinan . Selanjutnya, menurut Putusan Mahkamah Konstitusi No 46/PUU-VIII/2010, anak tersebut berhubungan dengan Tergugat secara perdata. Namun, dikarenakan Tergugat (Ayah biologis anak/suami siri Penggugat) masih terikat perkawinan sah dengan wanita lain serta dalam perkawinan yang dilakukan oleh Penggugat dan Tergugat tidak terbukti secara akta perkawinan, dan anak tersebut hanya diterima sebagai anak kandung secara biologis, bukan anak sah, karena secara perdata adalah anak hasil zina. Kata kunci: Perceraian, Kawin Siri, Status Anak Abstract: This study aims to examine the status of children in a siri marriage divorce as per Islamic Law and Positive Law in Indonesia. In this case, the husband is still legally married to another woman. Included in a normative legal study with a statutory and case approach, this study applies primary and secondary data. Through literature study techniques, the data in this study was analyzed using the syllogism deduction method. The findings of the study prove that the status of the child in Decision No. 546/Pdt.G/2024/PA.Krw can be legally recognized as the biological child of the Defendant (the biological father of the child/the Plaintiff's common-law husband) in accordance with the evidence submitted in court. Even though at the time of marriage, the Plaintiff (the child's mother/the Defendant's common-law wife) was two months pregnant, the child born can be recognized as the child of the Defendant (the biological father of the child/the Plaintiff's common-law husband), because the requirement that the child of a woman who is pregnant at the time of marriage as stated by Imam Syafi'i and Imam Malik is born at least six months after the marriage, while the child of the Plaintiff was born after seven months of marriage. Furthermore, according to Constitutional Court Decision No 46/PUU-VIII/2010, the child is civilly related to the Defendant. However, because the Defendant (the biological father of the Plaintiff's child/strict husband) was still legally married to another woman and the marriage between the Plaintiff and the Defendant was not proven by a marriage certificate, and the child was only borne by the Defendant. Keywords: Divorce, Unregistered Marriage, Child Status